MANGROVE ECOSYSTEM MANAGEMENT STRATEGY FOR TUNDA ISLAND, BANTEN PROVINCE - Alfiani, Titin; Choesin, Devi Nandita; Sofiatin, Sofiatin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Mangrove ecosystems protect small islands and provide economic and social benefits to the community. Among the small islands in Indonesia with mangroves at its shorelines is Tunda Island, located in Serang District, Banten Province. However, various threats, such as shipping industrial waste and climate change, have caused the mangroves of Tunda Island to decline. This study aims to describe the condition of mangroves on Tunda Island, assess the local community's perception level of mangrove management, and formulate a strategy for managing the mangrove ecosystem on this island. This research was conducted on Tunda Island, Banten Province in January 2022. Mangrove ecological data were collected at four stations using purposive sampling, and questionnaires were distributed to collect community social data from 95 respondents. Mangrove health was analyzed using the Mangrove Health Index (MHI), while community social data were analyzed using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis and the Quantitative Strategic Planning Matrix (QSPM). Results showed that the mangroves fall into the category of poor, with an MHI of 14.75% on the north side; poor with 17.16% on the west side; moderate with 51.07% on the south side; and moderate with 65.89% on the east side of the island. The level of community perception of Tunda Island mangrove management is 60.66%, which implies a positive perception, and that the people of Tunda Island have an adequate understanding of the role of the mangrove ecosystem. The priority management strategy is to empower the community in the accelerated program to rehabilitate sustainable mangrove ecosystems by providing equal opportunities and rights for the community.